Age differences in comprehension of the meaning of a short story - Almonaitienė , Junona; Steponavičiūtė , Aldona (Psichologija, 2000)
It has been considered nowadays that the text meaning is a many-layer phenomenon with a complex number of factors having influence on it. To concentrate on these problems, the level of short story comprehension predominant in different age groups was chosen as the focus of the study. The empirical research included three age groups, the eleven, fifteen and twenty year-olds, consisting of 24 persons each. They were provided with the text considered to be both attractive to all the groups and stimulating wide range of interpretations. The respondents were induced to interpret separate fragments of the story as well as the whole of it. Two independent judges identified each interpretation according to the following criteria: a comprehender's concentration on the events, on the heroes' feelings and their motivation, and on the underlying of the text. High coincidence of their decisions (0.83) was observed. The interpretations of both teenage groups most frequently dealt with the events, and also they displayed high concentration upon the heroes' feelings and their motivation. The oldest group produced significantly more suggestions of the text underlying. The demonstrated level of the text comprehension was not correlated with the subjective evaluation of the text’s attractiveness and perspicuity within all the groups. It was related to sex and the grades of the native language within the younger groups.
Keywords: short story; meaning of text; comprehension; age differencies